Optimal location and size of distributed generation to reduce power losses based on differential evolution technique - Abdul Wahab, Noor Izzri; Hammadi, Ahmed Sahib; Othman, Mohammad Lutfi (Universiti Putra Malaysia Press, 2017)
An electric power system generate electricity to meet demands. Distributed Generation (DG) allows electricity to be generated in a small capacity where the customer is located. In this paper, multi-objective functions based on the indices of system performance are formulated and used to determine the best location. The Differential Evolution technique (DE) has been employed to calculate optimal sizing for each location. Unity power factor DG model have been studied in this work and the problems solved with one DG unit. IEEE 14 bus has been used as a test system.